Resilient Entrepreneurs in the Digital Era: Strategic Marketing Approaches for Young Business Owners Amid Crisis - Nurhilalia, N.; Saleh, Yusuf (Manunggal Halim Jaya, 2025)
In an era marked by rapid digital transformation and recurrent global crises, young entrepreneurs face both unprecedented opportunities and significant challenges. This study explores how strategic digital marketing practices contribute to the resilience of youth-led enterprises amid crises such as economic downturns and pandemics. Drawing on a quantitative descriptive approach, the research aims to identify the most prevalent marketing strategies employed by young entrepreneurs and assess their perceived effectiveness in enhancing business resilience. Data were collected through structured surveys distributed to young business owners across various sectors who actively utilize digital platforms. The findings reveal that adaptive strategies such as content marketing, community engagement, platform-based analytics, and value co-creation play a central role in maintaining customer trust, sustaining operations, and enabling business recovery. Moreover, the results underscore that digital infrastructure readiness and entrepreneurial orientation significantly influence the successful implementation of these strategies. The study highlights the moderating role of ecosystem support and the constraining effects of burdens such as limited digital literacy and cybersecurity concerns. The implications of this research extend to policymakers, incubators, and digital training providers seeking to enhance the resilience and competitiveness of youth entrepreneurship in volatile digital economies. This study contributes to the growing body of literature at the intersection of digital entrepreneurship, strategic marketing, and resilience theory.